Tiling and somatotopic alignment of mammalian low-threshold mechanoreceptors - Kuehn, Emily D. (Proc Natl Acad Sci U S A, 2019)
Innocuous mechanical stimuli acting on the skin are detected by sensory neurons, known as low-threshold mechanoreceptors (LTMRs). LTMRs are classified based on their response properties, action potential conduction velocity, rate of adaptation to static indentation of the skin, and terminal anatomy. Here, we report organizational properties of the cutaneous and central axonal projections of the five principal hairy skin LTMR subtypes. We find that axons of neurons within a particular LTMR class are largely nonoverlapping with respect to their cutaneous end organs (e.g., hair follicles), with Aβ rapidly adapting-LTMRs being the sole exception. Individual neurons of each LTMR class are mostly nonoverlapping with respect to their associated hair follicles, with the notable exception of C-LTMRs, which exhibit multiple branches that redundantly innervate individual hair follicles. In the spinal cord, LTMR central projections exhibit rostrocaudal elongation and mediolateral compression, compared with their cutaneous innervation patterns, and these central projections also exhibit a fine degree of homotypic topographic adjacency. These findings thus reveal homotypic tiling of LTMR subtype axonal projections in hairy skin and a remarkable degree of spatial precision of spinal cord axonal termination patterns, suggesting a somatotopically precise tactile encoding capability of the mechanosensory dorsal horn.